Bringing in the "CIA": A New Process to Improve Staff Communication. Issue 6 (November 2015) - Hunter, Rebecca; Mitchell, Jinjer; Loomis, Elena
Abstract : Nurses consistently express dissatisfaction with the overwhelming amount and rate of change in health care today. Nurse educators identified this as a problem at a 475-bed hospital and developed a process to present changes in information in a new and exciting method. This article reports on the identification and implementation of the new communication model and the lessons learned during the process. A new method for communication dissemination was designed utilizing a "Coordinator Information Advisory Group" concept.